1990
DOI: 10.1073/pnas.87.20.7930
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and sequencing of the active site of 1-aminocyclopropane-1-carboxylate synthase.

Abstract: The pyridoxal phosphate (PLP)-dependent 1-aminocyclopropane-1-carboxylic acid (ACC) synthase (S-adenosyl-L-methionine methylthioadenosine-lyase, EC 4.4.1.14), the key enzyme in ethylene biosynthesis, is inactivated by its substrate S-adenosylmethionine (AdoMet). Apple ACC synthase was purified with an immunoaffinity gel, and its active site was probed with NaB3H4 or Ado[(4C]Met. HPLC separation of the trypsin digest yielded a single radioactive peptide. Peptide sequencing of both 3H-and 14C-labeled peptides re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
69
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 30 publications
0
69
0
1
Order By: Relevance
“…In wounded tomato fruit discs treated with CHI, Kende and Boller (10) (17) showed that the rate of ACC synthase inactivation in vitro depends upon the concentration of AdoMet and that in the presence of AVG, a competitive inhibitor of ACC synthase with respect to AdoMet (7), the half-life of the enzyme activity in vitro increases from 54 to 108 mmn. Later work showed that this AdoMet-dependent inactivation results from an irreversible covalent linkage of the 2-aminobutyrate moiety of AdoMet to the enzyme (18,25).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In wounded tomato fruit discs treated with CHI, Kende and Boller (10) (17) showed that the rate of ACC synthase inactivation in vitro depends upon the concentration of AdoMet and that in the presence of AVG, a competitive inhibitor of ACC synthase with respect to AdoMet (7), the half-life of the enzyme activity in vitro increases from 54 to 108 mmn. Later work showed that this AdoMet-dependent inactivation results from an irreversible covalent linkage of the 2-aminobutyrate moiety of AdoMet to the enzyme (18,25).…”
Section: Resultsmentioning
confidence: 99%
“…Spanu et al (21) 3B) and other previous data (26). It should be noted that both native and AdoMet-inacti-_4 vated ACC synthase proteins are recognized by the monoclonal antibody (17,25). Thus, if the inactivation of ACC synthase by AdoMet represents the first step in its turnover, this inactivated enzyme must be further degraded by a rapid proteolytic process (17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two enzymes, ACC synthase and ACC oxidase, are responsible for ethylene biosynthesis from its precursor S-adenosyl Met (Yang and Hoffman, 1984), and blocking the synthesis of these enzymes in antisense RNA experiments results in reduced ethylene synthesis (Hamilton et al, 1990;Oeller et al, 1991). Functional identification of cDNA clones encoding ACC synthase has been achieved by expression studies in Escherichia coli and yeast and by sequence comparisons to peptides purified from ACC synthase protein (Sato and Theologis, 1989;Yip et al, 1990;Dong et al, 1991).…”
mentioning
confidence: 99%
“…T h e predicted peptides of the broccoli, tomato, and apple clones were aligned (Devereux et al, 1984), and regions of high identity were found to correspond to conserved regions of other ACC synthases (Park et al, 1992). The pbroc3 cDNA contained a region with 83% amino acid identity (100% similarity based on conservative changes) with the peptide sequence identified as the active site of ACC synthase (Yip et al, 1990). Broccoli (Brassica oleraceae L. var ltalica cv Shogun).…”
mentioning
confidence: 99%